2011
DOI: 10.1258/ebm.2011.010041
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of serum proteins in acute ischemic stroke patients treated with acupuncture

Abstract: In the present study, we have investigated the effects of acupuncture on (1) serum protein expression that might have a beneficial effect on stroke patients and (2) the strength of limb muscles in stroke patients. A total of 35 acute ischemic stroke (IS) patients were divided into two groups, one receiving drug treatment alone and the other receiving electroacupuncture (EA) and drug treatment. EA treatment was performed on eight acupuncture points once a day for 10 consecutive days. Serum proteins were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…Interestingly, recent study indicated that elevated MBL levels could be considered as an independent stroke risk factor in Chinese population [46] . The elevated blood levels of C3 complement protein in IS patients have been reported earlier by us [47] , as well as by other research groups [48][49][50][51][52] . However, this is the first study demonstrated the increased hemolytic activity of C3 in the blood of IS-affected subjects.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, recent study indicated that elevated MBL levels could be considered as an independent stroke risk factor in Chinese population [46] . The elevated blood levels of C3 complement protein in IS patients have been reported earlier by us [47] , as well as by other research groups [48][49][50][51][52] . However, this is the first study demonstrated the increased hemolytic activity of C3 in the blood of IS-affected subjects.…”
Section: Discussionsupporting
confidence: 79%
“…Omics studies on the acupuncture effects on Parkinson's disease [21, 22, 25, 26], rhinitis [24, 27], osteoarthritis [28], spinal injury [29, 30], pain [18, 19, 23, 25], aging [31, 32], ischemia (ischemic stroke) [33, 34], parturition [35] functional dyspepsia [36, 37], and so forth indicated that the mechanism of acupuncture is involved in the regulation of many body systems and is mainly associated with NEI system (Figure 1). The nerve, endocrine, and immune systems are distributed over the body widely.…”
Section: Omics Researches Of Acupuncture Based On the Cognition Ofmentioning
confidence: 99%
“…EA efficacy has been studied by comparing levels of serum proteins in response to EA or drug treatments in acute ischemic stroke patients [11]. Patients were treated with EA at eight acupoints (MS6, BL10, GB20, LI4, PC6, B40, SP6, and ST36) once daily for ten consecutive days.…”
Section: Proteomic Studies Of Acupuncture In Diseasesmentioning
confidence: 99%
“…We found that the ST36 acupoint is the most widely used acupoints, and that it has multiple therapeutic functions and targets, including spinal cord injury [46], allergic rhinitis [56], analgesia [38], neuropathic pain [9, 47], antiaging [41], knee osteoarthritis [45], and acute ischemic stroke [11]. Different from other therapies, acupuncture treatments show variation in the transcriptional profiles and perceived effect of their subjects, whether rats [39] or humans [40].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation